Vibrationally resolved decay width of interatomic Coulombic decay in HeNe - Trinter, Florian; Williams, J. B.; Weller, M.; Waitz, M.; Pitzer, M.; Voigtsberger, J.; Schober, C.; Kastirke, G.; Müller, C.; Goihl, C.; Burzynski, P.; Wiegandt, F.; et al. (Physical review letters, 2013)
We investigate the ionization of HeNe from below the He 1s3p excitation to the He ionization threshold. We observe HeNe+ ions with an enhancement by more than a factor of 60 when the He side couples resonantly to the radiation field. These ions are an experimental proof of a two-center resonant photoionization mechanism predicted by Najjari et al. [Phys. Rev. Lett. 105, 153002 (2010)]. Furthermore, our data provide electronic and vibrational state resolved decay widths of interatomic Coulombic decay in HeNe dimers. We find that the interatomic Coulombic decay lifetime strongly increases with increasing vibrational state.
Gesehen am 10.02.2022